Impact of the M184V/I Mutation on the Efficacy of Abacavir/Lamivudine/Dolutegravir Therapy in HIV Treatment-Experienced Patients. (12th July 2019) - Olearo, Flaminia; Nguyen, Huyen; Bonnet, Fabrice; Yerly, Sabine; Wandeler, Gilles; Stoeckle, Marcel; Cavassini, Matthias; Scherrer, Alexandra; Costagiola, Dominique; Schmid, Patrick; Günthard, Huldrych F; Bernasconi, Enos; et al.
Abstract: Objective: The impact of the M184V/I mutation on the virological failure (VF) rate in HIV-positive patients with suppressed viremia switching to an abacavir/lamivudine/dolutegravir regimen has been poorly evaluated. Method: This is an observational study from 5 European HIV cohorts among treatment-experienced adults with ≤50 copies/mL of HIV-1 RNA who switched to abacavir/lamivudine/dolutegravir. Primary outcome was the time to first VF (2 consecutive HIV-1 RNA >50 copies/mL or single HIV-1 RNA >50 copies/mL accompanied by change in antiretroviral therapy [ART]). We also analyzed a composite outcome considering the presence of VF and/or virological blips. We report also the results of an inverse probability weighting analysis on a restricted population with a prior history of VF on any ART regimen to calculate statistics standardized to the disparate sampling population. Results: We included 1626 patients (median follow-up, 288.5 days; interquartile range, 154–441). Patients with a genotypically documented M184V/I mutation (n = 137) had a lower CD4 nadir and a longer history of antiviral treatment. The incidence of VF was 29.8 cases (11.2–79.4) per 1000 person-years in those with a previously documented M184V/I, and 13.6 cases (8.4–21.8) in patients without documented M184V/I. Propensity score weighting in a restricted population (n = 580) showed that M184V/I was not associated with VF or the composite endpoint (hazard ratio [HR], 1.27; 95% confidence interval [CI], 0.35–4.59 and HR 1.66; 95% CI, 0.81–3.43, respectively). Conclusions: In ART-experienced patients switching to an abacavir/lamivudine/dolutegravir treatment, we observed few VFs and found no evidence for an impact of previously-acquired M184V/I mutation on this outcome. Additional analyses are required to demonstrate whether these findings will remain robust during a longer follow-up. Abstract : In antiretroviral therapy-experienced patients on abacavir/lamivudine/dolutegravir, we observed few virological failures and found no evidence for an impact of previously-acquired M184V/I mutation on this outcome. Additional analyses are required to demonstrate whether these findings will remain robust during a longer follow-up.